Highly Sensitive On‐Skin Temperature Sensors Based on Biocompatible Hydrogels with Thermoresponsive Transparency and Resistivity. Issue 14 (24th May 2021) - Park, Tae Hyun; Park, Seongjin; Yu, Seunggun; Park, Sangun; Lee, Junseok; Kim, Sunho; Jung, Youngmee; Yi, Hyunjung
Abstract: The development of electrically responsive sensors that interact directly with human skin and at the same time produce a visual indication of the temperature is in great demand. Here, we report a highly sensitive electronic skin (E‐skin) sensor that measures and visualizes skin temperature simultaneously using a biocompatible hydrogel displaying thermoresponsive transparency and resistivity resulting from a temperature dependence of the strength of the hydrogen bonding between its components. This thermoresponsive hydrogel (TRH) showed a temperature dependence of not only the proton conductivity but also of its transmittance of light through a change in polymer conformation. We were able to use our TRH temperature sensor (TRH‐TS) to measure temperature in a wide range of temperatures based on a change in its intrinsic resistivity (−0.0289 °C −1 ) and to visualize the temperature due to its thermoresponsive transmittance (from 7% to 96%). The TRH‐TS exhibited high reliability upon multiple cycles of heating and cooling. The on‐skin TRH‐TS patch is also shown to successfully produce changes in its impedance and optical transparency as a result of changes in skin temperature during cardiovascular exercise. This work has shown that our biocompatible TRH‐TS is potentially suitable as wearable E‐skin for various emerging flexible healthcare monitoring applications. Abstract : Highly sensitive and biocompatible temperature sensors are demonstrated using a thermoresponsive hydrogel resulting from a temperature dependence of the strength of the hydrogen bonding between the components of the hydrogel. The reversible phase transition of the hydrogelenables an on‐skin temperature sensor patch showing changes in electrical resistance and optical transparency induced by changes in skin temperature during cardiovascular exercise.